Peran Asosiasi Depot Air Minum dan Petugas Sanitasi Puskesmas Terhadap Kondisi Sanitasi Depot Di Wilayah Kerja Puskesmas Nanggalo Tahun 2021 - Hidayathil Husna; Evino Sugriarta; Alsri Windra Doni (Jurnal Sehat Mandiri, 2022)
DAM is the third largest drinking water facility used by the people of West Sumatra (17.2%). The latest data in Padang City is about 627 DAM. The increasing public consumption of depot water production is not accompanied by supervision from the puskesmas. The research design used cross sectional. The research was conducted in the working area of ​​the Nanggalo Health Center, Padang City. Population 29 depots with total sampling technique. Data analysis used univariate and bivariate with Chi Square test. Results A total of 79.3% of drinking water depot sanitation has met the requirements, as many as 82.2%. Drinking water depot associations have played a role, as many as 64.5% of sanitation workers have played a role in achieving their goals, there is a significant relationship between the role of depot associations with depot sanitation conditions P = 0.000 and PR = 24 and there is a significant relationship between the roles of puskesmas sanitation workers and sanitation conditions depots in the working area of ​​the Nanggalo Health Center Padang City P = 0.011 and PR = 18. In conclusion, there is an influence of puskesmas sanitation workers with depot sanitation conditions in the working area of ​​Nanggalo Health Center Padang City in 2021. Suggestions are expected to have good cooperation between puskesmas sanitation workers and water depot associations drink to keep the water clean.